Determination of thermal focal length under different depths of focus in asymmetrical flat-flat dynamically stable resonators. (October 2018) - Wang, Hongli; Wang, Yulei; Zhang, Hengkang; Liu, Zhaohong; Lu, Zhiwei
Highlights: Overlap efficiency is insensitive to focus depth and changeless with waist size at small M2 pump. A measurement method of focal length for asymmetric flat-flat cavity is presented and validated. Output power is insensitive to telescope system and coupler transmission at small focus depth. Focal length difference between different focus depths is gradually reduced with pump power. Abstract: A theoretical and experimental investigation on mode matching efficiency and thermal focal length in LD end-pumped Nd:YAG laser is presented. The laser rod thermal distribution and the mode matching efficiency on the waist size and the focus depth with different pump beam qualities are analyzed. An easy-to-use measurement method to obtain the focal length of asymmetric flat-flat dynamic cavities is proposed and then focal lengths at different depths of focus are measured revealing focal length apparently decreases with the decreasing of focus depth. Experimental results show the output power is not sensitive to telescope system and output coupler transmission when the depth of focus is small. There are better mode matching and higher output power at small focus depth, but shorter focal length and worse output beam quality will occur in this case. So depth of focus should be optimized, considering thermal lens effect, to scale output power referring to the cavity design.